2019
DOI: 10.3390/molecules25010102
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Structure Modification on Luteolin-Cinnamic Acid Conjugates Leading to BACE1 Inhibitors with Optimal Pharmacological Properties

Abstract: BACE1 inhibitory conjugates derived from two natural products, luteolin (1) and p-hydroxy-cinnamic acid (2), were subjected to systematic structure modifications, including various positions in luteolin segment for conjugation, different linkers (length, bond variation), as well as various substitutions in cinnamic acid segment (various substituents on benzene, and replacement of benzene by heteroaromatics and cycloalkane). Optimal conjugates such as 7c and 7k were chosen on the basis of a series of bioassay d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Among all of the examined flavanones, hesperidin demonstrated the best inhibition of BACE-1, AChE, and BChE, with IC 50 values of 10.02, 22.80, and 48.09 µM, respectively. Kinetic studies revealed that all the flavanones were noncompetitive inhibitors of BACE-1 and cholinesterase [ 101 , 102 ].…”
Section: Flavonoids Attenuate Human Diseases Via Direct Interactiomentioning
confidence: 99%
“…Among all of the examined flavanones, hesperidin demonstrated the best inhibition of BACE-1, AChE, and BChE, with IC 50 values of 10.02, 22.80, and 48.09 µM, respectively. Kinetic studies revealed that all the flavanones were noncompetitive inhibitors of BACE-1 and cholinesterase [ 101 , 102 ].…”
Section: Flavonoids Attenuate Human Diseases Via Direct Interactiomentioning
confidence: 99%
“…One bio-effective constituent is cinnamic acid, a BACE1 inhibitor. Sun et al [ 72 ] have coupled cinnamic acid ( p -hydroxy-cinnamic acid) with the phytochemical luteolin to develop BACE1 inhibitors with greater effectiveness. While each of them is a non-competitive inhibitor, they each bind to different regions of BACE1 [ 65 ].…”
Section: Bace1 As a Phytochemical Targetmentioning
confidence: 99%
“…While each of them is a non-competitive inhibitor, they each bind to different regions of BACE1 [ 65 ]. A series of constructs resulted in a single flavone-cinnamic acid hybrid referred to as 7c (IC 50 1.44 × 10 −6 M) that should be further examined as a potential therapy for AD [ 72 ]. This approach of developing phytochemical conjugates could possibly guide the discovery of BACE1 inhibitors that are specific for AβPP1 leading to reduced levels of Aβ, while leaving other essential substrates untouched.…”
Section: Bace1 As a Phytochemical Targetmentioning
confidence: 99%
“…A later study found a linked conjugate of luteolin and p-hydroxy-cinnamic acid to be a highly potent, cellpermeable, and noncompetitive inhibitor of BACE1. 78 Further modification of this compound made it selective over other related enzymes such as BACE2 and rennin. Most of the initial BACE1 inhibitors were peptide-based and therefore cell impermeable and the challenge of generating one of the first natural scaffold-based cell-permeable inhibitors was addressed by Hwang et al They isolated lavandulyl flavanones from Sophora flavescens Aiton that show strong BACE1 inhibition in vitro as well as in human embryonic kidney cells.…”
Section: Flavonoids As Bace1 Inhibitorsmentioning
confidence: 99%
“…It was found that the flavonoid directly binds to BACE1 and also activates the estrogen receptor to reduce BACE1 transcription. A later study found a linked conjugate of luteolin and p -hydroxy-cinnamic acid to be a highly potent, cell-permeable, and noncompetitive inhibitor of BACE1 . Further modification of this compound made it selective over other related enzymes such as BACE2 and rennin.…”
Section: Flavonoids As Bace1 Inhibitorsmentioning
confidence: 99%